1999
DOI: 10.1097/00002030-199912030-00007
|View full text |Cite
|
Sign up to set email alerts
|

Do gender differences in CD4 cell counts matter?

Abstract: These gender differences in CD4 lymphocyte counts suggest a delay of initiation of therapy in women compared with men (our model predicted that women reach the threshold of starting HAART at about 12 months later than men). If this delay unfavourably influences progression, treatment guidelines should be revised so that women can benefit equally from HAART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
61
2
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(84 citation statements)
references
References 10 publications
20
61
2
1
Order By: Relevance
“…If R value is small, then it takes large errors. For R square 0.701, nearly one third the variation in viral load is explained by the independent variable cd4 cell count similar to other studies [5][6][7][8]. The viral load is inversely proportional to CD4 cell count [9,10].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…If R value is small, then it takes large errors. For R square 0.701, nearly one third the variation in viral load is explained by the independent variable cd4 cell count similar to other studies [5][6][7][8]. The viral load is inversely proportional to CD4 cell count [9,10].…”
Section: Discussionsupporting
confidence: 81%
“…Other studies have noted gender differences in viral loads and CD4 at various stages of the disease, where females develop AIDS at higher CD4 counts and lower viral loads [6][7][8].…”
Section: Discussionmentioning
confidence: 92%
“…Males from the Multicenter AIDS Cohort Study (MACS) with high CD4 counts prior to HIV infection had, compared to others, higher viral load, and steeper slope of CD4 counts decline in the early months following infection, so that there was no evidence for a beneficial effect of higher CD4 counts before infection (31). Also, it has been shown that females have higher CD4 counts than males at the time of HIV seroconversion, AIDS development, and death, without difference in survival compared to males (32). The significance of the findings shown in this paper should not therefore be interpreted in view of their potential impact on survival after HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Most programs and projects aiming to reduce drug-related harm still face political opposition and experience serious operational difficulties in many communities and countries 12 . More recently, with the introduction of highly active antiretroviral therapy (HAART) in developed countries (and a small number of developing countries), striking differences have been observed in the rates of progression of HIV infection within IDUs populations and between IDUs and other populations, due to differences in the spectrum of HIV-related illnesses, prevalence of different co-infections, access to health care, and adherence to HAART 13,14 .…”
Section: Introductionmentioning
confidence: 99%